2011
DOI: 10.1177/0309364610389351
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technology in developing countries

Abstract: Background: The ‘Convention on the Rights of Persons with Disabilities’ (CRPD) requires governments to meet the assistive technology needs of citizens. However, the access to assistive technology in developing countries is severely limited, which is aggravated by a lack of related services.Objectives: To summarize current knowledge on assistive technology for low- and lower-middle-income countries published in 1995 or later, and to provide recommendations that facilitate implementation of the CRPD.Study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 65 publications
5
67
0
2
Order By: Relevance
“…"Info: Vaccinations for children under 10 will be available tomorrow from [8][9][10][11][12] in the Codito sector" when a participant asked about a bacterial infection, the community clinician sent a response and also directed her to speak with a physician for further information.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…"Info: Vaccinations for children under 10 will be available tomorrow from [8][9][10][11][12] in the Codito sector" when a participant asked about a bacterial infection, the community clinician sent a response and also directed her to speak with a physician for further information.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Computer access provides a method of reading and writing, communication and education and with Internet access, computers can offer widespread information access and participation in the information society [7,6]. AT to access computers may include built-in universal access features or specialized technology [8]. Universal access features make computers usable by both the non-disabled population and people with disabilities, for instance, by changing a setting in the computer's operating system, repeated keystrokes can be ignored when someone who has a tremor is typing on a standard keyboard.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 60% of 1,414 disabled people reported using some form of assistive technology in their daily lives (Carlson and Ehrlich 2006) and the majority of carers of children with physical disabilities reported the use of assistive technology in the children's daily activities or routines (Kling, Campbell, and Wilcox 2010). In addition, Borg, Lindstrom, and Larsson (2011) reported that the literature on the use of assistive technology in developing countries was dominated by product-oriented research on leg prostheses and manual wheelchairs.…”
Section: Effects Of Self-help Support Groups and Assistive Technologymentioning
confidence: 99%
“…States who ratified the CRPD have the obligation "to take effective measures to ensure personal mobility with the greatest possible independence for persons with disabilities" (UN, 2006). Guidelines for the delivery of assistive technology in the best possible way exist (Borg et al, 2008;Arledge et al, 2011); the current challenge is to make these assistive devices and services available to the people with disabilities in developing countries, in an accessible and affordable manner (Borg et al, 2009;Tomlinson et al, 2009;Borg et al, 2011a). The CRPD explicitly mentions the need for international technical and economical collaboration between developing and developed countries, to improve the availability of assistive technology devices and services in developing countries (Borg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%